2023
DOI: 10.3389/fcell.2022.1079920
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction induced epigenetic effects on aging

Abstract: Aging is the subject of many studies, facilitating the discovery of many interventions. Epigenetic influences numerous life processes by regulating gene expression and also plays a crucial role in aging regulation. Increasing data suggests that dietary changes can alter epigenetic marks associated with aging. Caloric restriction (CR)is considered an intervention to regulate aging and prolong life span. At present, CR has made some progress by regulating signaling pathways associated with aging as well as the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 225 publications
0
5
0
1
Order By: Relevance
“…Recent discoveries in the anatomy of the facial fat compartment have conceptually and interventionally revolutionized the approach to adding volume to specific deflated soft tissue compartments, creating a more individualized youthful restoration of the face [48,49]. Rendering or even reconstructing the characteristics of facial youth starts from the skeletal structure and goes progressively up to the SMAS.…”
Section: Anatomical Base Of Modern Surgery-superficial Musculoaponeur...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent discoveries in the anatomy of the facial fat compartment have conceptually and interventionally revolutionized the approach to adding volume to specific deflated soft tissue compartments, creating a more individualized youthful restoration of the face [48,49]. Rendering or even reconstructing the characteristics of facial youth starts from the skeletal structure and goes progressively up to the SMAS.…”
Section: Anatomical Base Of Modern Surgery-superficial Musculoaponeur...mentioning
confidence: 99%
“…CR studies continued to develop throughout the 20th century. A 2020 study fed rats with fewer calories than their ad-libitum counterparts and found that 57% of the age-related genetic changes that occurred in normal rats did not occur in calorie-restricted rats [49]. MRI or CT imaging of SMAS are also evolving to demask its implications into the phenomena of the aging face [50][51][52].…”
Section: Anatomical Base Of Modern Surgery-superficial Musculoaponeur...mentioning
confidence: 99%
“…Eating an unhealthy diet with calorie excess will certainly promote the development of atherosclerosis, ISR, and ST [64]. CR protects DNA methylation, histone modification, and non-coding RNA (nc-RNA), which prevent VSMC proliferation, migration, and inflammation, which play an important role in developing atherosclerosis and ISR [65,66]. Most individuals who follow PBDs generally do not necessitate CR since these diets inherently promote a sense of satiety.…”
Section: Caloric Restriction Is An Essential Factor In Combating Infl...mentioning
confidence: 99%
“…Обмеження калорій (ОК) вважають найбільш фізіологічним індуктором аутофагії [40][41][42]. Зростає число даних про те, що старіння сповільнюють харчові продукти, які містять природні сполуки ресвератрол, катехіни (зокрема, ґаллат епіґаллокатехіну (повністю англійською, EGCG), який у великих кількостях присутній у чаї), екстракт прополісу, креозол і флавон лютеолозід (флавон, різновид флавоноїду).…”
Section: аутофагія в умовах обмеження калорійunclassified